Evaluation of Clinical Spectrum and Patterns of Abnormal Uterine Bleeding (AUB) in Perimenopausal Women. A Hospital-Based Study - Shazia, Mamoona Sarwar, Aysha Iqbal, Nazneen Akhtar, Farah Saleem, Abeerah Zafar (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Abnormal uterine bleeding (AUB) is one of the most common gynecological complaints among perimenopausal women and a leading cause of hospital visits. It significantly affects quality of life and may indicate underlying gynecological or systemic pathology. Understanding the clinical spectrum and bleeding patterns of AUB is essential for timely diagnosis and appropriate management. Objective: To evaluate the clinical manifestations, hematological status, and etiological causes of abnormal uterine bleeding among perimenopausal women aged 40–50 years. Methods: This cross-sectional study included 87 perimenopausal women presenting with abnormal uterine bleeding. Detailed clinical and menstrual histories along with physical examinations were recorded. Laboratory investigations included complete blood count, thyroid function tests, and relevant hormonal assays. Transvaginal ultrasonography was performed in all cases. Abnormal uterine bleeding patterns and etiologies were classified using the FIGO PALM–COEIN system. Data were analyzed to determine the prevalence of various bleeding patterns and underlying causes. Results: Heavy menstrual bleeding was the most frequent presentation, observed in 46% of participants, followed by intermenstrual bleeding (21%), prolonged bleeding (18%), and frequent cycles (15%). According to the PALM–COEIN classification, structural causes accounted for 55% of cases, with leiomyoma (27%) and endometrial polyps (15%) being the most common. Non-structural causes were identified in 45% of women, predominantly ovulatory dysfunction (28%) and coagulopathy or endocrine abnormalities (17%). Anemia was present in 42% of participants and was more frequent among women with heavy menstrual bleeding. Conclusion: Abnormal uterine bleeding in perimenopausal women exhibits a broad clinical spectrum, with heavy menstrual bleeding being the most common presentation. Both structural and non-structural etiologies play a significant role, emphasizing the importance of a systematic diagnostic approach using the PALM–COEIN framework. Early diagnosis and targeted management are crucial to reduce morbidity and improve quality of life in this population. Keywords: Abnormal uterine bleeding; Perimenopause; PALM–COEIN; Heavy menstrual bleeding; Leiomyoma; Ovulatory dysfunction.